Estimation of the refractivity gradient from measured essential climate variables in Iyamho-Auchi, Edo State, South-South Region of Nigeria - Kingsley Eghonghon Ukhurebor; Wilson Nwankwo (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Meteorological variables are crucial constituents in the estimation of refractivity disseminations and the uncharacteristic radio wave propagation situations of the troposphere as a result of their impact on radio wave communication relations over the atmosphere. In this study the measurement and assessment of air temperature, relative humidity and atmospheric pressure was carried out for a period of one year; 2018, so as to estimate the refractivity gradient over Iyamho-Auchi, Edo State, Nigeria using a self-implemented inexpensive portable meteorological monitoring device. The measurements of the essential climate variables were done at the administrative building of Edo University Iyamho by placing the meteorological monitoring device on a fixed position. The results show that the monthly estimated refractivity gradient values which would be useful in the prediction of the local radio propagation range from -20.00 N-units/km to -190.00 N-units/km with an average value of -60.67 N-units/km for the period under consideration. The findings also show that the months with limited relative humidity have greater refractivity gradient values compared to the ones with higher relative humidity. It was also observed from the results that the measured essential climate variables were having significant impacts on the estimated refractivity gradient during all the months in 2018, and these impacts were more noticeable in the months with higher relative humidity compared with the months that were having limited relative humidity.